SHAIKH KEMAS MUá¸¤AMMAD AZHARI (1856-1932): KARYA-KARYA DAN PEMIKIRAN ULAMA PALEMBANG: SHAIKH KEMAS MUHAMMAD AZHARI (1856-1932): WORKS AND THOUGHTS OF PALEMBANG SCHOLARS - Muhamad Rosadi (Penamas, 2015)
This paper presents the works and thoughts of a scholar from Palembang, namely Shaikh Kemas Muhammad Azhari with particular focus on one of his works in the field of reckoning. In addition to his reputation as an outstanding scholar in 18th century, Shaikh Muhammad Azhari is also famous as Palembang scholar in the late 19th and early 20th centuries, because of his works. This study uses documents from library and interviews with Shaikh Azhariâ€™relatives. This study found that Shaikh Azhari is one of the prominent scholars writers Palembang who continue kitab writing tradition as well as' Abd al-á¹¢amad alFalimbani. There are about 14 pieces of Shaikh Azhari works, covering a variety of disciplines such as Islamic beliefs, monotheism, jurisprudence, sufism and astronomy. Regarding his religious thought, Shaikh Azhari revealed the balance on the use of rukyah and reckoning methods in determining the beginning of the month of hijriyah as it is described in one of his works entitled TaqwÄ«m alQiyÄm. Keywords: Islamic thought, ulama, Shaikh Azhari, Palembang. Tulisan ini menyajikan tentang karya-karya dan pemikiran seorang ulama asal Palembang, yakni Shaikh Kemas Muhammad Azhari, dengan fokus pada satu karyanya di bidang hisab. Selain ulama Palembang abad ke-18 yang cukup terkenal, Shaikh Kemas Muhammad Azhari adalah juga seorang ulama Palembang yang cukup terkenal di akhir abad ke-19 dan awal abad ke-20, karena karya-karya tulisanya. Penelitian ini bersumber pada data-data kepustakaan dan wawancara dengan kerabat Shaikh Azhari. Penelitian ini menemukan, bahwa Shaikh Azhari merupakan salah satu tokoh ulama penulis Palembang yang melanjutkan tradisi penulisan kitab sebagaimana halnya â€˜Abd al-á¹¢amad al-Falimbani. Tercatat ada sekitar 14 buah karya Shaikh Azhari yang mencakup berbagai disiplin ilmu keislaman seperti aqidah, tauhid, fikih, tasawuf, dan falak. Adapun pemikiran keagamaan Shaikh Azhari yang terungkap antara lain mengenai keseimbangan penggunaan metode rukyah dan hisab dalam menentukan awal bulan hijriyah sebagaimana dijabarkan dalam salah satu karyanya yang berjudul TaqwÄ«m al-QiyÄm.Kata Kunci: Pemikiran Islam, ulama, Shaikh Azhari, Palembang